2013
DOI: 10.1016/j.jjcc.2012.08.020
|View full text |Cite
|
Sign up to set email alerts
|

Tolvaptan reduces the risk of worsening renal function in patients with acute decompensated heart failure in high-risk population

Abstract: In patients with ADHF with high risk of WRF, treatment with tolvaptan could prevent WRF compared to conventional therapy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
65
0
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 84 publications
(72 citation statements)
references
References 38 publications
6
65
0
1
Order By: Relevance
“…Propensity score matching analyses: The clinical use of TLV has increased recently, and many authors have showed that TLV is beneficial in ameliorating symptomatic congestion and in normalizing hyponatremia, thus improving renal function in patients with decompensated HF. [1][2][3][4][5][6][7][8][9][10][11][12][13][14][15][16][17][18] Therefore, prospective recruitment of a control group has thus far been ethically difficult considering the obvious clinical advantage of TLV treatment.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Propensity score matching analyses: The clinical use of TLV has increased recently, and many authors have showed that TLV is beneficial in ameliorating symptomatic congestion and in normalizing hyponatremia, thus improving renal function in patients with decompensated HF. [1][2][3][4][5][6][7][8][9][10][11][12][13][14][15][16][17][18] Therefore, prospective recruitment of a control group has thus far been ethically difficult considering the obvious clinical advantage of TLV treatment.…”
Section: Discussionmentioning
confidence: 99%
“…[1][2][3][4][5][6][7][8][9][10][11][12][13][14] Although the long-term efficacy of TLV remains controversial, 6) we recently demonstrated the benefits of long-term administration of TLV on survival and re-admission, especially in responders to TLV. 15) Despite its clinical advantage, TLV is expensive compared with other conventional diuretics, which is an important limitation considering current increases in total medical expenses.…”
mentioning
confidence: 99%
“…34 Several studies reported on the effectiveness of the combined use of tolvaptan and furosemide in HF patients with renal dysfunction. 35, 36 Thus, tolvaptan may have beneficial effects in HF patients with reduced eGFR who need high-dose loop diuretics.…”
Section: Combination Of Raas Inhibitors and β-Blockers With Loop Diurmentioning
confidence: 99%
“…24 A recent small study in patients with AHF and low baseline GFR showed that tolvaptan, when added to furosemide, was associated with superior decongestion and considerably less WRF with lower doses of furosemide. 26 In the EVEREST trial, patients randomized to tolvaptan also were given lower doses of furosemide, despite persistent lower body weight, 24 stable renal function, and no other safety concerns. The available clinical data along with the mechanistic issues, therefore, suggest that a larger, longer term trial of this drug in patients with AHF and WRF would be feasible at this time.…”
Section: Circ Heart Failmentioning
confidence: 99%